2012
DOI: 10.1144/sp367.13
|View full text |Cite
|
Sign up to set email alerts
|

On the nucleation of non-Andersonian faults along phyllosilicate-rich mylonite belts

Abstract: The weakness of fault zones is generally explained by invoking an elevated fluid pressure or the presence of extremely weak minerals in a continuous fault gouge horizon. This allows for faults to slip under an unfavourable normal to shear stress ratio, in contrast to E. M. Anderson’s theory of faulting. However, these mechanisms do not explain why faults should nucleate in such an orientation as to make them misoriented and non-Andersonian. Here we present a weakening mechanism, involving the mechanical anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
4
22
0
Order By: Relevance
“…We suggest that high differential stresses caused by the contrast in effective viscosity between quartz veins and the surrounding phyllonite promoted crystalplastic deformation by sub-grain rotation, similar to that described by Trepmann and Stöckhert (2009). Bons (1988) showed that chlorite can deform by dislocation creep at temperatures as low as c. 250 • C. Crystal plastic deformation in chlorite and other phyllosilicates is attained by very easy glide along the (001) slip planes, whereas dislocation climb and the activation of hard slip systems is facilitated by kinking and diffusion (Bons, 1988). We suggest that crystal plastic creep became an effective deformation mechanism in the KF as temperatures exceeded c. 250 • C in the UpP.…”
Section: Structural Evolution Of the Kvenklubben Fault: A Synopsissupporting
confidence: 58%
See 1 more Smart Citation
“…We suggest that high differential stresses caused by the contrast in effective viscosity between quartz veins and the surrounding phyllonite promoted crystalplastic deformation by sub-grain rotation, similar to that described by Trepmann and Stöckhert (2009). Bons (1988) showed that chlorite can deform by dislocation creep at temperatures as low as c. 250 • C. Crystal plastic deformation in chlorite and other phyllosilicates is attained by very easy glide along the (001) slip planes, whereas dislocation climb and the activation of hard slip systems is facilitated by kinking and diffusion (Bons, 1988). We suggest that crystal plastic creep became an effective deformation mechanism in the KF as temperatures exceeded c. 250 • C in the UpP.…”
Section: Structural Evolution Of the Kvenklubben Fault: A Synopsissupporting
confidence: 58%
“…The ability of phyllonitic fault rocks to deform by stable creeping has been attributed elsewhere to either increased fluid pressures (Rice, 1992), frictional grain sliding Tesei et al, 2012), pressure solution (Gratier et al, 2011), dislocation creep (Bons, 1988) or a combination of these mechanisms (e.g. Bos and Spiers, 2002).…”
Section: Structural Evolution Of the Kvenklubben Fault: A Synopsismentioning
confidence: 99%
“…Such assemblages are likely to display anisotropy in their frictional behaviour. Bistacchi et al (2012) extend the slip tendency analysis of Morris et al (1996) to rocks with directional variations in frictional resistance to sliding. Improved laboratory characterization of rock mechanical properties is the basis for several recent approaches to brittle fracture in the crust, representing another departure from Andersonian orthodoxy.…”
Section: Low-angle Structures and The Nature Of Stress Variations Witmentioning
confidence: 88%
“…These models could be extended to analyse in more detail the situation reported in Tingay et al (2012), exploring the parameter space for controlling stress rotations above and below a detachment within the sediment package. Bistacchi et al (2012) develop a novel model of low-angle detachment instability due to anisotropic coefficients of sliding friction. Many low-angle detachments contain zones of strongly aligned fabrics defining an intense structural anisotropy, with these local fabrics oriented parallel to the detachment.…”
Section: Low-angle Structures and The Nature Of Stress Variations Witmentioning
confidence: 99%
“…The regional-scale exhumation of the Tauern window associated to the extensional activity of the Brenner Fault Zone (Behrmann, 1988;Bistacchi, Massironi, Menegon, Bolognesi, & Donghi, 2012;Massironi, Bistacchi, & Menegon, 2011;Selverstone, 1988) resulted in cooling of the Penninic units and transition from ductile to brittle deformations. This is evidenced by a penetrative west-dipping, top-down SC fabric developed in the ridge between Vipiteno and Spina del Lupo, corresponding to the footwall of the Brenner Line, which is hidden by Quaternary deposits in the Isarco valley (small outcrops around Vipiteno and the Brenner Pass).…”
Section: Tectonic Evolutionmentioning
confidence: 99%